Proposal of an audit-based model for implementation of energy management in SMES - Luiz Vieira, Everton; Eduardo Gouvêa da Costa, Sergio; Pinheiro de Lima, Edson (International Journal of Sustainable Energy Planning and Management, 2025)
Energy Management has become a matter of utmost importance for organizations worldwide, many of which are implementing energy management solutions to comply with regulations, improve their usage, and enhance their reputation with their customers. Typically, in SMEs - small and medium-sized enterprises, the culture of Energy Management is incipient, leading to energy waste due to poor strategic and operational management. This research aimed to develop a model to support the implementation of an energy management program based on audits. A conceptual model was developed for conducting audits, analyzing the electricity consumption of equipment, using the multicriteria method Promethee-ROC to rank recommendations from the IAC - Industrial Assessment Centers database, proposing performance indicators, and finally, analyzing the performance of the proposed model and its applicability. The procedural model was developed using the Process Approach methodology to construct a model that will assist in the audit process, analysis, recommendations, and decision-making. A case study was conducted in a small plastic injection company, where the model was tested and refined. As a result, the company obtained a ranking of recommendations according to its reality, along with a set of indicators and tips for implementing an EMS based on ISO 50001 and literature. The manager’s perception of the process was also evaluated, yielding results all above good in terms of usability, feasibility, and usefulness for the proposed model.